241 LEFT ATRIAL SEPTAL POUCH THROMBOSIS AFTER COVID19 INFECTION: IS IMMUNOTHROMBOSIS THE CULPRIT MECHANISM?. (15th December 2022) - Morello, Matteo; Maestroni, Alerto; Matteo, Federica; Tavano, Elisa; Rossetti, Giuseppe; Franzoni, Irene; Crenna, Marco; Sgaria, Riccardo; Golino, Michele; De Ponti, Roberto
Abstract: Aims: The atrial septal pouch (ASP) is an incomplete fusion between septum primum (SP) and septum secundum (SS), resulting in a kangaroo pouch, that has a high prevalence in general populations (47%) and it is a potential site of blood stasis and thrombosis. After the novel coronavirus disease (COVID19) -related thrombotic complications, immunothrombosis has been widely investigated and proposed as key pathogenic mechanism linking coagulation and inflammation, leading sometimes to intracardiac thrombosis. In this paper we describe a case of thrombus in the ASP interestingly developed after COVID19 and made a literature review. Methods and Results: A 85 years old woman with a history of hypertension and chronic atrial fibrillation (AF) in therapy with dabigatran, was admitted to our hospital for dyspnea, atypical chest pain and fever. Laboratory exams showed only mild leukocytosis and elevated levels of d-dimer; EKG confirmed AF with a normal ventricular rate and CT scan excluded pulmonary embolism. Transthoracic and transesophageal echocardiogram (TEE) (Figure 1) showed a mobile ovoid mass (13×26 mm) attached to a left-sided ASP mimicking a myxoma, no mass was seen in the left atrial appendage (LAA). Four months earlier she had been hospitalized for idiopathic thrombocytopenia and concurrent COVID19 infection with mild symptoms, therefore dabigatran was discontinued for a month. The patient underwent surgery and histopathology confirmed it was a thrombus. In the PubMed search we conducted for reports demonstrating ASP masses, or alleged thromboembolism (TE) from this site, we found 25 reports, whose characteristics are briefly summarized in Table 1. Interestingly mild thrombocytopenia was described just in one case. Table 1 Total N=25 Age (mean ± standard deviation) 61, 4 ± 12, 5 Female n= 7/25 (28%) Atrial fibrillation (AF) n= 13/24(53.2%) Anatomical variant: Left-sided ASP n= 23/25 (92%) Right-sided ASP n= 1/25 (4%) Webbed ASP n= 1/25 (4%) Type of mass: Thrombus n= 19/25 (76%) Alleged embolization n= 5/25 (20%) Lipoma n= 1/25 (76%) History of stroke n= 11/25 (44%) Symptomatic TE n= 13/25 (52%) Conclusions: In addition to the LAA, the atrial septal pouch is a newly described, common anatomic entity of the interatrial septum, that potentially serves as a site of stasis and thrombus formation. Despite its high prevalence, the finding of a thrombus in this site is very rare. According to Virchow triad, we assume that in this case an endothelial injury and hypercoagulability could have played a pivotal role, since the concomitant thrombocytopenia and high levels of d-dimer. This could be the first case of a thrombus in the ASP associated with COVID19-immunothrombosis.